A real-time RT-PCR for detection of clade 1 and 2 H5N1 influenza A virus using locked nucleic acid (LNA) TaqMan probes - Thanh, T; Pawestri, H; Ngoc, N; Hien, V; Syahrial, H; Trung, N; Wertheim, H; Chau, N; Ha, D; Van Doorn, H; Farrar, J; Hien, T; et al. (BioMed Central, 2010)
The emergence and co-circulation of two different clades (clade 1 and 2) of H5N1 influenza viruses in Vietnam necessitates the availability of a diagnostic assay that can detect both variants. RESULTS: We developed a single real-time RT-PCR assay for detection of both clades of H5N1 viruses, directly from clinical specimens, using locked nucleic acid TaqMan probes. Primers and probe used in this assay were designed based on a highly conserved region in the HA gene of H5N1 viruses. The analytical sensitivity of the assay was < 0.5 PFU and 10-100 ssDNA plasmid copies. A total of 106 clinical samples (58 from patients infected with clade 1, 2.1 or 2.3 H5N1 viruses and 48 from uninfected or seasonal influenza A virus-infected individuals) were tested by the assay. The assay showed 97% concordance with initial diagnostics for H5 influenza virus infection with a specificity of 100%. CONCLUSIONS: This assay is a useful tool for diagnosis of H5N1 virus infections in regions where different genetic clades are co-circulating.